Addressing critical knowledge gaps to improve and shorten multidrug-resistant tuberculosis treatment regimens in children - Garcia-Prats, Anthony Joseph (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.